Process simulation and quality evaluation of incremental sheet forming - Echrif, Salah B. M.; Hrairi, Meftah (IIUM Press, 2011)
Single Point Incremental Forming (SPIF) is a promising sheet-metal-forming process that permits the manufacturing of small to medium-sized batches of complex parts at low cost. It allows metal forming to work in the critical ‘necking-to-tearing' zone which results in a strong thinning before failure if the process is well designed. Moreover, the process is complex due to the number of variables involved. Thus, it is not possible to consider that the process has been well assessed; several remaining aspects need to be clarified. The objective of the present paper is to study some of these aspects, namely, the phenomenon of the wall thickness overstretch along depth and the effect of the tool path on the distribution of the wall thickness using finite element simulations.